Research Institute of Pediatrics and Children’s Health in Petrovsky National Research Centre of Surgery - Leyla S. Namazova-Baranova; Eduard T. Ambarchyan; Vladislav V. Ivanchikov; Anastasia D. Kuzminova; Anna G. Shandra; Elena A. Vishneva; Grigorii V. Revunenkov; Kirill A. Valyalov (Вопросы современной педиатрии)
Background. Psoriasis is an independent risk factor for cardiovascular diseases (CVD). One of the markers associated with the CVD course is epicardial fatty tissue (EFT) that is thicker in psoriasis patients. EFT assessment can be used as a useful indicator of CVD in psoriasis patients. The data about the effect of genetically engineered biological therapy (GEBT), used for psoriasis management, on the EFT thickness is limited. Examination of GEBT effects on EFT may improve our understanding of CVD prevention in psoriasis patients.Objective. The aim of the study is to study the changes in EFT thickness on GEBT.Methods. A prospective cohort study included 56 children with severe and moderate psoriasis. Patients underwent transthoracic two-dimensional echocardiography (M-mode) with EFT thickness assessment and PASI (Psoriasis Area and Severity Index) scoring before the GEBT initiation. All the parameters were re-evaluated after 16 weeks. All patients were divided into three groups according to the initiated therapy: adalimumab, secukinumab and ustekinumab. When dividing the therapy received into groups, the age of the patients was taken into account: inclusion in the adalimumab group was carried out from 4 years, in the secukinumab and ustekinumab groups — from 6 years. Otherwise, the process of group assignment was random. The study results were processed using descriptive statistics methods: the changes in EFT thickness in individual groups were compared via the Wilcoxon test, and results were considered statistically significant at p 0.05.Results. Before the start of therapy, in 56 patients the mean of EFT thickness was 2.11 mm, the mean PASI — 18.32. The adalimumab group had the following indicators: the mean EFT thickness before the therapy was 2.1 mm, and it has decreased to 1.77 mm after 16 weeks of therapy. The mean change in EFT thickness was 0.33 mm, and the median — 0.17 mm [CI 0.33 ± 0.25]. The ustekinumab group: the mean EFT thickness before the therapy was 2.13 mm, 16 weeks after — 1.69 mm. The mean change in EFT thickness was 0.44 mm, and the median — 0.38 [CI 0.44 ± 0.13]. The secukinumab group: the mean EFT thickness before the therapy was 2.08 mm, 16 weeks after — 1.82 mm. The mean change in EFT thickness was 0.27 mm, and the median — 0.27 [CI 0.27 ± 0.07]. Evaluation of indicators via Wilcoxon test has shown statistically significant decrease in the EFT after therapy in all groups (p 0.05). 73% of patients achieved PASI 50, and 6% — PASI 75 in the adalimumab group. 21% of patients did not achieve PASI 50. The mean PASI score before therapy was 16.73 points, and after 16 ± 4 weeks — 6.4 points, the mean dynamics was 10.33 points, the median dynamics was 7 points [CI 10.33 ± 4]. All patients achieved PASI 50, 75.3% — PASI 75, 8% — PASI 90, and 16.7% — PASI 100 in the ustekinumab group. The mean PASI score before therapy was 22.17 points, and after 16 weeks — 3.67 points, the mean dynamics was 19.28 points, the median dynamics was 17 points [CI 18.5 ± 3.03]. All patients achieved PASI 50, 47% — PASI 75, and 11% — PASI 90 in the secukinumab group. The median PASI before therapy was 14.29 points, and after 16 ± 4 weeks — 3.71 points, the mean PASI score before therapy was 14.29 points, and after 16 weeks — 3.7 points, the mean dynamics was 10.59 points, the median dynamics was 10 points [CI 10.59 ± 2.27]. Evaluation of indicators via Wilcoxon test has shown statistically significant decrease in the PASI after therapy in all groups (p 0.05). There were no adverse events leading to cessation of therapy during the follow-up period.Conclusion. All groups have shown decrease in the in EFT thickness and in the PASI score. The most significant dynamics was observed in the ustekinumab group. Research limitations were the small patients sample and the absence of a control group (participants without psoriasis).